Chondromalacia of the cranial medial femoral condyle; its occurrence and association with clinical outcome in a population of adult horses with stifle lameness. (5th December 2019) - Croxford, A. K.; Parker, R. A.; Burford, J. H.; Lloyd, D.; Boswell, J. C.; Hughes, T. K.; Phillips, T. J.
Summary: Background: Chondromalacia of the cranial medial femoral condyle (CMFC) is a potential cause of stifle lameness in adult horses. However, there is scant published evidence of either its occurrence or its clinical significance. Objectives: To document the occurrence of CMFC seen during diagnostic arthroscopy in adult horses with stifle lameness and to investigate its prognostic significance. Study design: Retrospective cohort study. Methods: The records were reviewed of all horses with unilateral or bilateral lameness localised to the stifle that underwent diagnostic arthroscopy of the cranial medial femorotibial joint at a UK equine hospital. The surgical findings were noted from each. Case outcomes were determined by unstructured telephone discussions with owners. A satisfactory outcome was defined as a horse that was in ridden work without ongoing anti‐inflammatory medication. Multivariable logistic regression was used to create a model with an outcome time point at 12‐month post‐operatively. Results: One hundred and four horses were included in the study. CMFC was found in 79. In 25 CMFC was the only finding, 54 horses had CMFC plus other pathology and 25 had other pathology, but no CMFC. At 12 months, horses with CMFC were 9.9 (95% CI 2.2–45.0, P<0.01) times more likely to have an unsatisfactory outcome than horses without CMFC. Main limitations: The study relied on retrospective analysis of clinical notes and archived arthroscopy videos. Assessment of outcome was determined by unstructured telephone interview and therefore there is potential for reporting errors to exist. Conclusions: CMFC is a common arthroscopic finding in horses with stifle lameness and is significantly associated with an increased likelihood of the horse not being in ridden work at long‐term follow‐up.